Factor Xa inhibitors versus low molecular weight heparin for the treatment of cancer associated venous thromboembolism; A meta-analysis of randomized controlled trials and non-randomized studies. (January 2022) - Hussain, Maryam R.; Ali, Faisal S.; Verghese, Dhiran; Myint, Phyo Thazin; Ahmed, Mubashir; Gong, Zimu; Gerais, Yasmin; Siddiqui, Mahrukh; Lin, Jenny J.; Troy, Kevin
Graphical abstract: Highlights: The effectiveness and safety of NOAC use in CA-VTE remains unclear beyond composite endpoints of VTE and overall bleeding events. Our analysis of the literature found a reduced risk of recurrent VTE as a composite endpoint, with no significant difference in the risk of recurrent pulmonary embolism with NOAC use compared to low molecular weight heparin. The risk of overall bleeding events was consistently higher with NOAC use, whereas the risk of major bleeding events was higher in the non-randomized literature. High certainty evidence guiding management decisions is needed to further characterize the safety and efficacy profile of NOACs for the treatment of CA-VTE. Abstract: Introduction: We compared the safety and efficacy of Xa-inhibitors to LMWH for treatment of venous thromboembolism in mixed and gastrointestinal cancer cohorts (CA-VTE). Methods: A systematic search identified RCTs and non-randomized studies (NRS) comparing Xa-inhibitors to LMWH for treating CA-VTE. Relative risks were computed. Certainty was assessed using the GRADE approach. Results: Xa-inhibitors reduced the risk of recurrent VTE (RR0.64;0.49-0.84) and NRS (RR0.74;0.60-0.92;Moderate-Low Certainty). There was no significant difference in recurrent PE in RCTs (RR0.72;0.50-1.02) and NRS (1.43;0.65-3.12;Low-Very Low Certainty). Xa-inhibitors increased the risk of overall bleeding events in RCTs (RR1.45;1.05-2.01) and NRS (RR1.72;1.42-2.08;Moderate-Low Certainty), and the risk of major bleeding events in NRS (RR1.56;1.17-2.07), but not in RCTs (RR1.33;0.94-1.89; Low-Very Low Certainty). Similar results were detected in gastrointestinal cancer patients. Conclusion: Xa-inhibitors may reduce the risk of recurrent VTE, but not recurrent PE compared to LMWH. A higher overall bleeding risk, and a questionably higher major bleeding risk was found with Xa-inhibitor use.